2021
DOI: 10.5577/intdentres.2021.vol11.suppl1.33
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liquid sorption and color stability of dental composites after exposure to common lactation teas

Abstract: Aim: To assess the effects of common lactation teas on liquid sorption and color stability of three different dental composites. Methodology: A total of 60 samples (n = 5) were examined from three composite materials: Omnichroma (Tokuyama Dental Co., Tokyo, Japan), Estelite Posterior, (Tokuyama Dental Co., Tokyo, Japan), and Mosaic Universal (Ultradent production Inc., South Jordan, UT, USA). Samples measuring 2x6 mm were taken and immersed in three different teas—Humana (Humana, Bremen, Germany), Hipp, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
3
7
0
Order By: Relevance
“…This result could be due to the adsorption and absorption of the yellow stains, which have low polarity. This low polarity of yellow stain can penetrate deeper layers of resin composite [ 21 ], in agreement with many studies [ 4 , 16 ]. On the opposite side, a study found an acceptable color change after immersion in coffee for 48 h E < 3.3; this may be due to differences in immersion solution preparation methods and concentration [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This result could be due to the adsorption and absorption of the yellow stains, which have low polarity. This low polarity of yellow stain can penetrate deeper layers of resin composite [ 21 ], in agreement with many studies [ 4 , 16 ]. On the opposite side, a study found an acceptable color change after immersion in coffee for 48 h E < 3.3; this may be due to differences in immersion solution preparation methods and concentration [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…Recently, many manufacturers introduced a new single-shade resin composite as it has the advantage of reducing chair time and shade selection time [ 15 ]. Moreover, it was reported that any discoloration in the resin composite would affect the aesthetic [ 16 , 17 ]. Hence, the current study presented the problems of color stability of resin composite after exposure to commonly consumed drinks of different storage periods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations